2022
DOI: 10.3389/fcell.2022.702224
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis-Related Signature and Tumor Microenvironment Infiltration Characterization in Head and Neck Squamous Cell Carcinoma

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is the sixth most widespread and deadly cancer. Until now, very few studies have systematically evaluated the role of pyroptosis-related genes (PRGs) and lncRNAs in HNSCC patients.Methods: We integrated the genomic data to comprehensively assess the role of pyroptosis with the tumor microenvironment cell-infiltrating characteristics in HNSCC. In addition, we also constructed a set of the scoring system to calculate the pyroptosis dysfunction in each pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Previous studies have suggested that OSER1-DT is downregulated in non-small cell lung cancer (NSCLC) and hepatocellular carcinoma (HCC) and acts as a tumor suppressor by regulating the expression of genes such as Smad2, Rab23, and ELAVL1 through microRNA sponging or competitive binding [ 43 ]. Additionally, OSER1-DT may modulate the expression of GPX4, a key regulator of ferroptosis, which is another form of regulated cell death that is distinct from necroptosis but may share some common regulators or modulators [ 44 ]. In this study, we found that the expression of OSER1-DT was positively correlated with plasma cell infiltration and the activation of most immune pathways, particularly the B-cell receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that OSER1-DT is downregulated in non-small cell lung cancer (NSCLC) and hepatocellular carcinoma (HCC) and acts as a tumor suppressor by regulating the expression of genes such as Smad2, Rab23, and ELAVL1 through microRNA sponging or competitive binding [ 43 ]. Additionally, OSER1-DT may modulate the expression of GPX4, a key regulator of ferroptosis, which is another form of regulated cell death that is distinct from necroptosis but may share some common regulators or modulators [ 44 ]. In this study, we found that the expression of OSER1-DT was positively correlated with plasma cell infiltration and the activation of most immune pathways, particularly the B-cell receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies combined genomic data from bladder cancer and head and neck squamous cell carcinomas to classify pyroptosis into different subtypes. The results further confirmed prognosis and immunotherapy sensitivity differences between patients with different tumor subtypes [ 49 , 50 ]. This finding corroborates the findings of the present study.…”
Section: Discussionsupporting
confidence: 69%
“…In fact, the use of bioinformatics to find biomarkers to predict the prognosis of patients by different characteristics of tumors is very common in many types of tumors (46)(47)(48). However, due to the many influencing factors involved, it is often difficult to summarize the results with deterministic significance.…”
Section: Discussionmentioning
confidence: 99%